Perceived formal authority and the effectiveness of the HR department in Vietnam. Issue 2 (7th March 2019) - Nguyen, Diep T.N.; Teo, Stephen T.T.; De Cieri, Helen; Ho, Marcus
Abstract : Purpose: The purpose of this paper is to investigate whether formal authority of the HR department has any impact on line managers' evaluations of HR department effectiveness. Design/methodology/approach: Two studies were conducted in Vietnam. Study 1 comprised a survey of 405 line managers to test the hypothesized model. Study 2 comprised a survey conducted with 155 line managers validated the findings from Study 1. Structural equation modeling and PROCESS macro were used to analyze the data. Findings: Line managers' perceptions of the HR department's formal authority had a positive and indirect impact on HR department effectiveness through the HR department's strategic involvement and influence. Public sector line managers tended to perceive their HR departments as possessing a higher level of formal authority than did their private sector counterparts. Research limitations/implications: This study extends the theory of political influence as it applies to the HR department. Specifically, the study provides empirical evidence of the influences of an organization's political conditions on the perceptions of HR department effectiveness. This study also contributes to the extant literature on HRM in Vietnam by showing how Vietnam's HR departments can utilize power and influence in accordance with specific ownership types. Practical implications: Public sector HR managers could establish their formal authority among stakeholders as a way to enhance the recognition of HR department effectiveness. This can be done by relying on the presence of the traditional bureaucratic characteristics of the public sector which confer the HR department with formal authority. Originality/value: The study contributes an understanding of the determinants of HR department effectiveness in the context of Vietnam. Research findings show that highly formal authority practices in the public sector affect the way line managers perceive the strategic involvement of the HR department. The more formal the authority, the more the public sector HR department is perceived to be involved in the strategic management process. Thus, formal authority is a prerequisite that public sector HR departments need to signal its importance among line managers. To have a long-term influencing role in the organization, the HR department in the public sector needs to develop its political and influencing skills. In contrast to this, the private sector HR department needs to develop a strategic partnership with line managers in order to increase its influence and perceived effectiveness.